Study of Immune Status for Rubella, Cytomegalovirus, Hepatitis B Virus, and Toxoplasma gondii in Sera of University Students - Saif A.J. Al-Shalah; Doaa Adil Abood; Sarah Kassab Shandaway Al-Zamali; Israa Habeeb Nasser; Laith A.I.K. Al-Kaif (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study was conducted to know the range of spread of Rubella virus, Cytomegalovirus, Hepatitis B virus,and Toxoplasma gondii among students at Al-Mustaqbal University College, its impact on society in theprovince of Babylon. Therefore this study includes the evaluation of the immune status in sera of studentsto the investigation from Toxoplasma gondii, Rubella virus, Cytomegalovirus by IgM/IgG rapid test andHepatitis B virus by HBV-5 rapid test of 90 specimens that were collected during the period extending fromJanuary 2019 to March 2019. Data about individuals have been collected aseptically in sterile containers,after getting all data in the special formula including, name, gender, age. It revealed that Cytomegalovirusformed (CMV) 13.3% followed by Toxoplasma gondii 0% Rubella 0%, depending on IgM. While showsresult in IgG seropositivity to Rubella was 60% followed by CMV was 36.7% and Toxoplasma was 10%.The results of the present study showed that all HBs Ag and HBe Ag were negative whereas HBe Ab andHBc Ab were positive, while HBs Ab was only three positive from other samples.